Selenium and tellurium in the development of novel small molecules and nanoparticles as cancer multidrug resistance reversal agents - Domínguez-Álvarez, Enrique; Rácz, Bálint; Marć, Małgorzata Anna; Nasim, Muhammad Jawad; Szemerédi, Nikoletta; Viktorová, Jitka; Jacob, Claus; Spengler, Gabriella (Drug resistance updates, 2022)
Selenium is an essential trace element that is crucial for cellular antioxidant defense against reactive oxygen species (ROS). Recently, many selenium-containing compounds have exhibited a wide spectrum of biological activities that make them promising scaffolds in Medicinal Chemistry, and, in particular, in the search for novel compounds with anticancer activity. Similarly, certain tellurium-containing compounds have also exhibited substantial biological activities. Here we provide an overview of the biological activities of seleno- and tellurocompounds including chemopreventive activity, antioxidant or pro-oxidant activity, modulation of the inflammatory processes, induction of apoptosis, modulation of autophagy, inhibition of multidrug efflux pumps such as P-gp, inhibition of cancer metastasis, selective targeting of tumors and enhancement of the cytotoxic activity of chemotherapeutic drugs, as well as overcoming tumor drug resistance. A review of the chemistry of the most relevant seleno- or tellurocompounds with activity against resistant cancers is also presented, paying attention to the synthesis of these compounds and to the preparation of bioactive selenium or tellurium nanoparticles. Based on these data, the use of these seleno- and tellurocompounds is a promising approach in the development of strategies that can drive forward the search for novel therapies or adjuvants of current therapies against drug-resistant cancers.
Keywords: mnohočetná léková rezistence; protinádorové látky; nádory; Drug Resistance, Multiple; Tellurium; reaktivní formy kyslíku; selen; telur; Antineoplastic Agents; Nanoparticles; Humans; Reactive Oxygen Species; lidé; Selenium; chemorezistence; Drug Resistance, Neoplasm; Neoplasms; nanočástice